Reclaiming history: dehumanization and the failure of decolonization. Issue 11 (17th October 2019) - Boucher, David
Abstract : Purpose: The purpose of this paper is to show, with reference to the writings of important decolonization theorists and liberationists, how Nazism in Europe and the establishment of the UN had a significant impetus in awakening the sense of injustice in colonised peoples in Africa and the Lesser Antilles. Colonized peoples were denied human rights through a process of dehumanization, which involved seizing "native" histories and representing them as backward, depraved and savage, awaiting the arrival of European civilization. Marxism, further supported this narrative by denying that "primitive" peoples had histories, and being unable to account for race and racism because of its emphasis on class. Colonization evolved, not into decolonization, but neo-colonialism because of the complicity of "native" bourgeois elites. Design/methodology/approach: The methodology combines historical narrative with theoretical insight from the point of view of the colonised, such as Fanon, Cabral, Mimmi, Ceasare, Nkrumah, etc. It is hermeneutic in its methodology. Findings: Peoples of the Lesser Antilles and Africans were dehumanized; denied human rights; and dehistoricized. Prominent liberation theorists develop these themes and reject elements of Marxism in order to reflect the unique experiences of the colonised. Colonization gets under the skin of the colonised and persists in contemporary societies. Colonization was replaced by neo-colonialism, not decolonization. Research limitations/implications: The implications are to bring to the fore the importance of colonialism in relation to western practises of anti-Fascism and the promotion of human rights, while perpetrating Fascist modes of behaviour and denying human rights in colonised countries. Far from being simply an historical phenomenon the insidious implications persist. Social implications: The demonstration of how deep the roots of colonialism go, and how difficult the task of decolonization has become as a consequence of systematic western "penetration". Originality/value: It looks at colonialism and its widespread injustices through the activists who suffered at the hands of a system of rule based exploitation and dehumanization effected not only by seizing their land, but also their history language and culture, ensuring that decolonization became transformed into neo-colonialism.